Association between grip strength and the risk of heart diseases among European middle-aged and older adults - Peralta, Miguel Pedro Fernandes de Almeida Fragoso (2021)
ABSTRACT - Background: The association between grip strength (GS) and heart diseases (HD) incidence has been little explored. Additionally, to the best of our knowledge, no previous study was performed in a multi-country European sample. Thus, the aim of this study is to analyse the longitudinal relationship between GS and the diagnosis of HD in European middle-aged and older adults. Methods: A prospective cohort study was conducted using data from the Survey of Health, Ageing and Retirement in Europe (2004-2017), including 20829 middle-aged and older adults from 12 countries. GS was objectively measured by a dynamometer and HD diagnosis was self-reported. Incidence rate of HD was calculated and a Cox proportional hazard regression was performed. Results: The HD incidence rate decreased from 930 per 100 000 person-years in the lowest quartile to 380 per 100 000 person-years in the highest GS quartile. During the 13 years of follow-up, compared to being in the lowest GS quartile, being in the highest quartile decreased the hazard of being diagnosed with a HD in 36% (95% confidence interval [CI]: 0.53, 0.78) for the whole sample, 35% (95% CI: 0.51, 0.84) for men and 46% (95% CI: 0.40, 0.73) for women. Conclusion: GS seems to be inversely associated with the incidence of HD among European middle-aged and older adults. Scientific evidence has highlighted the potential role of GS as a risk stratifying measure for HD, suggesting its potential to be included in the cardiovascular risk scores used in primary care. However, further research is still needed to clarify it.